ANALISIS KEBIJAKAN MANAJEMEN MEDATA KOLEKSI DIGITAL MAJALAH MANGLE DI PUSAT BUDAYA SUNDA UNVERSITAS PADJADJARAN - Aliffatin Nisa Nur Faidza; Elnovani Lusiana; Kusnandar Kusnandar (CV. Denasya Smart Publisher, 2026)
This study aims to analyse the metadata management policy of the Mangle Magazine digital collection at the Sunda Cultural Center of Padjadjaran University. Metadata management involves managing a structured digital object to describe, identify, and facilitate information retrieval so that it can be used in the long term. The method used is qualitative descriptive using a qualitative approach. Data collection techniques were conducted through primary and secondary data. Primary data was obtained through participatory observation and interviews, while secondary data was obtained through documentation studies from existing metadata reports, journals, and legal sources that can be used as references. Data analysis refers to information management theory, digital information systems, and metadata theory. The results of this study indicate that the management of the Mangle Magazine digital collection is not yet carried out systematically and in a standardised manner. The main issues include inconsistent metadata entry, particularly in the rubrication elements, and the absence of policies related to the management of metadata for the digital collection of Mangle magazine. The existing metadata cannot yet represent the information sources, thus hindering the information retrieval process. Therefore, metadata management policies need to be developed based on the uniqueness of Mangle magazine as the oldest local Sundanese cultural magazine, so that the digital Mangle magazine can serve as a cultural information source for future use.